Combining wind power and farmed fish: Coastal community perceptions of multi-use offshore renewable energy installations in Europe. (March 2022) - Billing, Suzannah-Lynn; Charalambides, George; Tett, Paul; Giordano, Michelle; Ruzzo, Carlo; Arena, Felice; Santoro, Anita; Lagasco, Fabrizio; Brizzi, Giulio; Collu, Maurizio
Abstract: There is increasing competition for space in coastal seas as new industrial sectors, such as Marine Renewable Energy (MRE) and Aquaculture, seek to expand. Multi-Use - involving sharing of space and, in some cases, facilities - can lessen competition and reduce industry costs if societal and economic challenges can be overcome. An example societal challenge is that of gaining Social Licence to Operate (SLO) for 'Multifunctional Offshore Installations' (MOI) combining fish farming with MRE (from wind and waves) in a large floating structure. This article reports a mixed-methods study at two potential MOI deployment sites in 2019, aiming to understand the local context for SLO. A survey was carried out in Reggio Calabria, Italy, with 108 respondents, and in Islay, Scotland, with 127 respondents. Questions concerned opinions about MRE and fish-farming, separately and combined. A facilitated workshop in Reggio Calabria provided additional qualitative data. Most findings were the same in both places. Respondents thought better of MRE than fish-farming but remained moderately likely to eat fish produced in MOI. The majority distrusted regulators to control environmental impacts of the technology. The main differences were that respondents in Reggio Calabria anticipated local benefits from MOI industrial activity, and were more likely to accept development by non-local owners than were people on Islay. We interpreted the findings in a conceptual framework that combines theory for SLO with theory for Action Situations, hypothesising that a community's diffuse and perhaps heterogenous opinions might 'crystalise' around an issue during an Action Situation. The hypothesis will be tested when a prototype MOI is deployed near Reggio Calabria in 2021.